Makātīb-i Akbar : Lisānulʻaṣr Akbar Allāhābādī marḥūm ke adab parvar ḵẖut̤ūt̤, 1909 se 1921 tak - Akbar Allāhābādī, 1846-1921 (SAMP early 20th-century Indian books project, 1922)
Collection of letters.